Regenerated wool keratin-polybutylene succinate nanofibrous mats for drug delivery and cells culture. (September 2020) - Guidotti, G.; Soccio, M.; Posati, T.; Sotgiu, G.; Tiboni, M.; Barbalinardo, M.; Valle, F.; Casettari, L.; Zamboni, R.; Lotti, N.; Aluigi, A.
Abstract: Keratin (Ker) protein regenerated from readily available and low-cost wastes (e.g. raw wool, feathers and textile by-products) is a promising natural polymer for tissue engineering and drug delivery. Nevertheless, while showing good bioactivity and great drug carrier properties, keratin lacks of suitable mechanical characteristics. To overcome this drawback, keratin was blended with poly(butylene succinate) (PBS), a biodegradable and biocompatible polyester able to confer mechanical integrity to the keratin based materials. Despite the poor compatibility at the molecular level between keratin and PBS, their 50-50 blends were successfully electrospun into manageable mats, made of randomly oriented nanofibers with mean diameter of 290 nm. Along with mechanical properties, PBS improves also the thermal stability of the keratin based nanofibrous mats. On the other hand, compared to PBS-only electrospun mats, the presence of keratin improves both swelling ability and biodegradability and amplifies the capacity of drug release as well as fibroblast proliferation of the blend mat. Highlights: Immiscible Keratin-polybutylene succinate (PBS) solution has been successfully electrospun. Homogeneous nanofibers of about 290 nm were obtained. PBS confers mechanical properties and thermal stability to the keratin-based nanofibrous mat. Keratin confer higher swelling and biodegradability to the keratin-based nanofibrous mat. Keratin stimulates the fibroblast adhesion and growth.